New concepts in heart failure with preserved ejection fraction and hypertension. (11th September 2022) - Joury, Abdulaziz; Gupta, Tripti; Krim, Selim R.
Abstract : Purpose of review: Hypertension (HTN) remains the most common and strongest contributing factor to the development of heart failure with preserved ejection fraction (HFpEF). In this review, we aim to summarize the pathophysiological processes linking HTN to HFpEF and highlight novel concepts in medical and device-based management of HFpEF and HTN. Recent findings: Despite the global increase in the prevalence of HFpEF, there has been limited benefit in current medication and device-based therapy for this complex syndrome. The hallmark of HFpEF is an elevated left intra-atrial and ventricular pressure and exertional dyspnea. Traditional medications used for treating HTN in patients with reduced left ventricular ejection fraction have unclear benefits in patients with HFpEF. Careful analysis of emerging medications such as angiotensin receptor–neprilysin inhibitor and sodium–glucose co-transporter-2 inhibitors showed benefit in reducing not only blood pressure but also hospitalizations in patients with HFpEF. Current data on device-based therapy aims to reduce left intra-atrial pressure, ventricular pressure and stimulate baroreceptors to lower blood pressure; however, needs further investigation. Summary: The nexus of HTN and HFpEF remains strong and complex. Although traditional medications for treating HFrEF did not affect long-term outcomes, novel therapies with angiotensin receptor neprilysin-inhibitor and sodium-glucose co-transporter-2 inhibitor offer promising results. Many device-based interventions in the HFpEF population are being developed with the aim to reduce left intra-atrial and ventricular pressure; however, their role in HFpEF hypertensive patients needs to be further investigated.